Run. Train. Race: Practical distance running advice for runners of all levels based on 50 years of running, teaching, and coaching - Fischer, J. (Techniques Magazine, 2024)
When you are in a race, here is a checklist: relaxation, pace, race position and strategy, form, rhythm, and easy, even breathing. You especially need to think about these things when you are tired. Keep your head level and your eyes up unless footing is a problem. Don´t look back. Instead, focus on catching the person ahead of you. That doesn´t mean you can´t look back to be aware of who is behind you. However, some constantly look back, interrupting their focus on what is ahead. Assume that someone is behind you and will attempt to pass you at the end of the race. Go hard through the finish. Some other things you can think about to mix things up a little are taking risks to test fitness, thinking of strategy to block you from thinking of the pain, learning what to do from different positions in the pack, working toward the next runner, looking at the runner´s shoulders and not their feet, running over the top of hills, surging and learning when to and when not to use it, paying attention to other runner´s breathing, and relaxing and getting into a natural rhythm to fight off a "bad patch" mid-race. This list isn´t all-inclusive.